The military-civilian gap and function of Army public affairs as an intermediary - Morelock, Anna M. (Kansas State University, 2008)
This case study explores the gap in attitudes, information and contact between soldiers and civilians and what Army public affairs officers do to try and bridge that gap. The study was exploratory and as such, brought up more questions than it answered. In-depth interviews were conducted with three Army public affairs officers from three different Army installations. A total of five community leaders from towns surrounding the installations also were interviewed. Most of the comments from public affairs officers and community leaders were positive. While the public affairs officers felt they could do a better job telling the Army’s story if they had more resources, the community leaders didn’t necessarily feel they were missing out on information. Some stereotypes or biases were detected in comments suggesting the Army was only interested in helping itself and on the flip side that there are just some things civilians would not understand. Further research on the military-civilian gap, particularly the gaps between certain demographics, would be usefully not only in helping public affairs officers target their messages but also in helping military recruiters better connect with possible enlistees.
Keywords: Military-civilian gap; Army public affairs; Case study; Mass Communications (0708)